THE THE BODY AS A SENSORY EXPERIENCE AND THE INCOMPLETENESS OF CHILDHOOD MEMORY IN THE CHARACTER LÍBIA MOIRÃ, BY CONCEIÇÃO EVARISTO - Colares Xavier, Laura (Revista (Entre Parênteses), 2025)
This article explores the relation between memory in the short story “Líbia Moirã”, from Insubmissas Lágrimas de Mulheres, by Maria da Conceição Evaristo de Brito, and the theoretical concepts presented by Mary Ann Doane in “Escala e Corpo no e para além do cinema”, as well as the notions of “subjectivity” and “incompleteness” found in Roland Barthes, A Câmara Clara. Through a literary approach and drawing on the aforementioned texts, the analysis focuses on the presence of Doane’s concept of the “human body as a sensory experience” within the story. Central to the narrative is the emergence and re-signification of a memory originating in the protagonist's childhood—the memory of her mother giving birth to Líbia's younger brother—which persists throughout her life. The general aim of this study is to reveal the impact of bodily memory traces on the character’s life trajectory. More specifically, it examines how the human body is portrayed as a sensory experience in the narrative and explores the presence of Barthes' notion of incompleteness as applied to Líbia Moirã’s dream-film-memory.